1994
DOI: 10.1007/bf02012732
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile chronic arthritis: Imaging of the knees and hips before and after intraarticular steroid injection

Abstract: Intraarticular steroid therapy in juvenile chronic arthritis (JCA) is performed because of high local efficacy with few side effects. Imaging is used for initial evaluation and for monitoring of treatment response. The aim of this study was to compare imaging findings in diseased hips and knees before and after therapy. A prospective study was performed on 10 patients (15 joints) scheduled for intraarticular therapy. Pretherapeutic assessment included clinical work-up, radiographs, ultrasound (US), and magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 7 publications
1
47
0
1
Order By: Relevance
“…We have now shown that as in adult arthritic joints [3], developing human joints also have a prominent lymphatic network. It is recognized that cartilage degradation products are cleared by the lymphatic system in arthritis, and this can lead to autoantigen production and perpetuation of inflammatory arthritis in mice [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…We have now shown that as in adult arthritic joints [3], developing human joints also have a prominent lymphatic network. It is recognized that cartilage degradation products are cleared by the lymphatic system in arthritis, and this can lead to autoantigen production and perpetuation of inflammatory arthritis in mice [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…É desencadeado por lesão e conseqüente reação inflamatória inespecí-fica da sinóvia, com infiltração moderada de células mononucleares e fibroblastos (8,11,12) . Não há relatos da presença de célu-las malignas nos tecidos gordurosos e sinovial de pacientes com LA (5,13) .…”
Section: Discussionunclassified
“…One study demonstrated a positive correlation between capsule distention of the hip as measured by MSK-US and increased intracapsular pressure and severe synovitis revealed on arthroscopy [34]. Another study using MRI and US to monitor the response of ten JCA patients to intra-articular steroid (IAS) injections of the knees and hips concluded that US was as sensitive as MRI in detecting pannus and/or effusion before IAS injection, although US distinction between the two entities was less clear compared with MRI [35]. El-Miedany et al compared x-ray, US and MRI findings in the knees of 38 patients with clinically active JIA and also in ten healthy control patients.…”
Section: Comparison With Other Imaging Modalitiesmentioning
confidence: 91%